2019
DOI: 10.2106/jbjs.18.00356
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Exchange Protocol for Periprosthetic Joint Infection Following Total Knee Arthroplasty in 245 Knees without Prior Treatment for Infection

Abstract: Background: For patients undergoing 2-stage exchange for the treatment of periprosthetic joint infection (PJI) following total knee arthroplasty, the long-term risk of reinfection and mechanical failure and long-term clinical outcomes are not well known. The purpose of our study was to determine the long-term clinical results of 2-stage exchange for PJI following total knee arthroplasty. Methods: We identified 245 knees that had undergone total knee art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
69
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 25 publications
10
69
4
1
Order By: Relevance
“…We included 30 patients (18 male, 12 female, 11 hips, 19 knees) that underwent complete two-stage exchange in our department. The mean age of our cohort was 70.5 years (range: 28–97 years), the mean body mass index was 30.7 kg/m 2 (range: 21.9–48.4 kg/m 2 ) and the mean days between both stages were 85.6 days (range 56–177 days). Because of the corona pandemic the time till replantation was in some cases longer than planned.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We included 30 patients (18 male, 12 female, 11 hips, 19 knees) that underwent complete two-stage exchange in our department. The mean age of our cohort was 70.5 years (range: 28–97 years), the mean body mass index was 30.7 kg/m 2 (range: 21.9–48.4 kg/m 2 ) and the mean days between both stages were 85.6 days (range 56–177 days). Because of the corona pandemic the time till replantation was in some cases longer than planned.…”
Section: Resultsmentioning
confidence: 97%
“…Prosthetic joint infection (PJI) is a serious complication that can occur after total joint arthroplasty (TJA). While there are different surgical approaches depending on various clinical factors 1 , two-stage revision with staged, subsequent reimplantation is widely considered the reference standard for treatment of chronic PJIs 2 , 3 . During the first stage all components are removed, a thorough synovectomy and debridement of the infected tissue is performed.…”
Section: Introductionmentioning
confidence: 99%
“…The average time between the 2 revision surgeries was 32 months. Petis et al [5] also recently reported reinfection rate of 4% at 1-year and up to 14% at 5-year in a 245-patient cohort. Most arthroplasty surgeons would consider 2 years to be the minimum follow-up required for the treatment of infection.…”
mentioning
confidence: 84%
“…Periprosthetic joint infection (PJI) is one of the severe complications of total knee arthroplasty (TKA), accounting for 25%-38% of postoperative complications in TKA [14]. Although through a series of measures [58] (including the use of perioperative antibiotics, intraoperative antibiotic cement, intraoperative antibiotic calcium sulfate, improvement of surgical environment, and elimination of local bacterial colonization), the infection rate has been controlled at about 1%-3% [9, 10]. However, with the rapid growth of the population undergoing TKA in recent years, the number of people with PJI has also increased annually [11, 12].…”
Section: Introductionmentioning
confidence: 99%